2012
DOI: 10.5070/v425110504
|View full text |Cite
|
Sign up to set email alerts
|

California Gull Predator Management and Reproductive Success of Endangered California Least Terns in the San Francisco Bay, California

Abstract: Gull predation is known to be an important source of egg and chick mortality for many waterbirds and can have severe impacts on recovery efforts for special status species. We evaluated the effectiveness of California gull management and removal by monitoring tern hatching and fledgling success annually. From 2005 to 2011, nesting success was monitored at a newly established California least tern colony at Hayward Regional Shoreline in San Francisco Bay. No gull management was undertaken prior to 2007. Califor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Oro et al () also found that individual yellow‐legged gulls ( Larus michahellis ) specialized on storm‐petrels ( Hydrobates pelagicus ), and gulls accounted for up to 33% of storm‐petrel mortality. Accordingly, seabird productivity tends to increase in studies that lethally remove the gulls that specialize on depredating eggs and chicks (Hario , Guillemette and Brousseau , Riensche et al ; but see Donehower et al ). Culling large populations of gulls had more variable success for improving waterbird populations and requires continual gull control measures (Thomas , Harris and Wanless , Anderson and Devlin ).…”
Section: Discussionmentioning
confidence: 99%
“…Oro et al () also found that individual yellow‐legged gulls ( Larus michahellis ) specialized on storm‐petrels ( Hydrobates pelagicus ), and gulls accounted for up to 33% of storm‐petrel mortality. Accordingly, seabird productivity tends to increase in studies that lethally remove the gulls that specialize on depredating eggs and chicks (Hario , Guillemette and Brousseau , Riensche et al ; but see Donehower et al ). Culling large populations of gulls had more variable success for improving waterbird populations and requires continual gull control measures (Thomas , Harris and Wanless , Anderson and Devlin ).…”
Section: Discussionmentioning
confidence: 99%
“…Although some of this shift in use may be the result of enhancements made to managed ponds, the large decreases observed in the use of specific salt ponds suggest that changes were more likely driven by a reduction in the habitat value of the remaining salt ponds, many of which are high-salinity ponds (> 120 ppt at the time of the 2019 survey) and are still used for salt production. High-salinity ponds can support abundant populations of invertebrate prey (Ephydra brine flies and Artemia brine shrimp) that often are exploited by American Avocets, Black-necked Stilts, and California Gulls (Larus californicus; Carpelan 1957;Herbst 2006;Takekawa et al 2009); however, those ponds are generally above the salinity tolerance of the fish on which Terns feed, which are limited to low-and medium-salinity ponds (Carpelan 1957;Mejia et al 2008;Peterson et al 2018;Riensche et al 2018). Forster's Terns have been shown to preferentially forage in lower-salinity pond habitat (Bluso- Demers et al 2016), and salinity was an important factor that determined overall pond use for both Forster's Terns and American Avocets .…”
Section: Discussionmentioning
confidence: 99%